Family functioning and adolescent internalizing symptoms: A latent profile analysis. (April 2018) - Simpson, Emily G.; Vannucci, Anna; Ohannessian, Christine McCauley
Abstract: This study aimed to characterize adolescent family functioning typologies using latent profile analysis (LPA). A secondary aim was to examine profile associations with adolescent internalizing symptoms at one-year follow-up. Students (N = 1029; 53% female; mean age = 16.14, SD = .75 years) completed measures of family functioning, anxiety, and depressive symptoms at two time points. LPA was conducted to characterize family functioning typologies at Time 1, revealing five profiles: 1) Low Family Functioning, 2) Only Close to Father, 3) Average Family Functioning, 4) Only Close to Mother, and 5) High Family Functioning. Results indicated that the Low and Only Close to Mother profiles had greater depressive symptoms at Time 2, compared with the Average profile. The High profile had fewer depressive symptoms at Time 2. The Low and Only Close to Mother profiles also had significantly more anxiety symptoms at Time 2. Findings highlight the utility of examining family functioning profiles. Highlights: Latent Profile Analysis revealed five family functioning profiles. 1) Low, 2) Only Close to Father, 3) Average, 4) Only Close to Mother, and 5) High. No demographic differences for adolescent gender, age, race, or parent education. Low and Mother Profiles had higher internalizing symptoms at Time 2.